A Comparative Analysis of Traditional and Decentralized Storage Systems in the Digital Age - Po Abbas Sunarya; Desy Apriani; Ruli Supriati; Danang Surya Budi; John Edwards (Pandawan, 2026)
The background of this research originates from the critical role of data storage in the advancement of modern digital technology, where centralized traditional cloud storage models have become dominant due to their accessibility and ease of data management. However, the challenges faced by these models include limited scalability, high operational costs, and vulnerabilities related to data security and privacy. In response to these limitations, the InterPlanetary File System (IPFS) has emerged as a decentralized storage solution that offers an alternative approach to data storage and distribution. The objective of this study is to compare IPFS and traditional cloud storage based on four key aspects: scalability, security, cost, and performance. The methodology involves a literature review and case studies of IPFS implementation in various practical scenarios. The findings reveal that while IPFS offers superior decentralization and resistance to data censorship, it still suffers from inefficiencies in data re- trieval and challenges in large-scale adoption. The results show that traditional cloud storage demonstrates advantages in access speed and integration capabilities but remains constrained by higher costs and the risks associated with data centralization. The conclusion emphasizes the need for continued research to enhance the efficiency of IPFS and to explore hybrid storage models that integrate the benefits of both decentralized and centralized technologies.